Determinants of Stunting in Children Aged 12-59 Months - Julianti, Erna; Elni, Elni (Department of Nursing, Faculty of Medicine, Diponegoro University, 2020)
Background: Stunting is one of the priority nutritional issues in Indonesia. It is one of the chronic malnutrition effects in children which will have a long-term impact on the growth and cross-generation of mothers through the cycle of stunting syndrome.Purpose: This study aimed to identify the determinant factors of stunting in children aged 12-59 months.Methods: Quantitative research with a cross-sectional approach was employed in this study, involving 205 respondents recruited using a consecutive sampling technique. Data were collected using the z scores and questionnaires for children aged 12-59 months, food trust questionnaire, feeding practice questionnaire and child eating habits questionnaire. The Chi Square test and multivariable logistic regression were performed for the data analysis.Results: Children who were not exclusively breastfed and had major infectious disease had a higher risk of stunting for 53.8% and 40.9%, respectively. There was a significant relationship between the history of exclusive breastfeeding (p=0.001, OR=2.28), the history of infection (p=0.013, OR= 2.27), and eating habits (p=0.04, OR=1.55) with stunting in children.Conclusion: There is a relationship between the history of exclusive breastfeeding, the history of infection and eating habits of children with stunting. The formation of a peer group community of children aged 12-59 months is expected to prevent and overcome stunting and improve nutritional status and optimal development of the children.